Pembuatan Biodiesel dari Minyak Jelantah Sebagai Solusi Pengurangan Limbah - Dewi Seprianingsih; Bayu Hidayatulrohman; Nur Amalina; Izmi Marsuci Nazla (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The increased consumption of frying oil in the Taliwang community of West Sumbawa County generates copious amounts of crude oil waste that can potentially pollute the environment if disposed of indiscriminately. This study aimed to utilize nectar oil as biodiesel feedstock through a transesterification process using KOH base catalyst. Results showed that biodiesel could be produced with a rendering of 78–85%, and physical characteristics such as golden yellow color and typical odor. The utilization of crude oil into biodiesel proved to be effective in reducing waste while providing an environmentally friendly energy source.